What Are the Regulatory Considerations for AI Drug Discovery? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2020)
Artificial intelligence (AI) is rapidly transforming the landscape of drug discovery and development, promising to accelerate the identification of new thera...
Keywords: Drug Discovery and Pharmaceutical AI; Regulatory; Considerations; Discovery; Artificial Intelligence